Berberine regulates the Notch1/PTEN/PI3K/AKT/mTOR pathway and acts synergistically with 17-AAG and SAHA in SW480 colon cancer cells. (1st January 2021) - Li, Ge; Zhang, Chuang; Liang, Wei; Zhang, Yanbing; Shen, Yunheng; Tian, Xinhui
Abstract: Context: Berberine (BBR) is used to treat diarrhoea and gastroenteritis in the clinic. It was found to have anticolon cancer effects. Objective: To study the anticolon cancer mechanism of BBR by connectivity map (CMAP) analysis. Materials and methods: CMAP based mechanistic prediction was conducted by comparing gene expression profiles of 10 μM BBR treated MCF-7 cells with that of clinical drugs such as helveticoside, ianatoside C, pyrvinium, gossypol and trifluoperazine. The treatment time was 12 h and two biological replications were performed. The DMSO-treated cells were selected as a control. The interaction between 100 μM BBR and target protein was measured by cellular thermal shift assay. The protein expression of 1–9 μM BBR treated SW480 cells were measured by WB assay. Apoptosis, cell cycle arrest, mitochondrial membrane potential (MMP) of 1–9 μM BBR treated SW480 cells were measured by flow cytometry and Hoechst 33342 staining methods. Results: CMAP analysis found 14 Hsp90, HDAC, PI3K or mTOR protein inhibitors have similar functions with BBR. The experiments showed that BBR inhibited SW480 cells proliferation with IC50 of 3.436 μM, induced apoptosis, autophage, MMP depolarization and arrested G1 phase of cell cycle at 1.0 μM. BBR dose-dependently up-regulated PTEN, while inhibited Notch1, PI3K, Akt and mTOR proteins at 1.0–9.0 μM ( p  < 0.05). BBR also acted synergistically with Hsp90 and HDAC inhibitor (0.01 μM) in SW480 cells at 0.5 and 1.0 μM. Discussion and conclusions: The integrative gene expression-based chemical genomic method using CMAP analysis may be applicable for mechanistic studies of other multi-targets drugs.